The development of a virtual life laboratory data management system - Srihawech, Thitaree; Busarathid, Kanchana; Pitsachart, Nualyai; Saenprasarn, Penchun; Busarathid, Jarut (NU Journal of Nursing and Health Sciences, 2021)
Teaching and learning in the discipline of nursing in the 21st century emphasizes the need of taking action in order to learn from real-life scenarios. Students’ critical thinking skills will increase as a result of using technology in teaching and learning. as well as resolving issues in nursing practice. The design of this study is research and development (R&D),aimed to 1) Design and create a virtual living laboratory Data Management System 2) Evaluate the virtual living laboratory data management system’s efficiency 3) Evaluate the virtual living laboratory data management system’s satisfaction.Thesample grouphad specific selection criteria consisted of 30 persons. The research instruments consisted of 1) the research tool was a data management system, that is, virtual life laboratory which was conducted by the technology experts 2) the data collection tool, the researcher developed from the literature review under the validation of five experts. The Data Management System of the Virtual Life Laboratory’sevaluation form. content consistency efficiency was content validity index (CVI) = 1.0. The confidence of Cronbach’s alpha coefficient was .85. The Satisfaction Assessment of the virtual life laboratory data management system’sevaluation form CVI was 1.0. Cronbach’s alpha coefficient confidence was .95. Data was analyzed using frequency, percentage, mean, and standard deviation. The results showed that 1) the overall virtual life laboratory data management system efficiencywas a high-level acceptance of database system quality(Mean = 3.83, SD. = 0.72). 2) The Satisfaction information management system of the virtual life laboratory was at a high level (Mean = 3.79, SD. = 0.82). Summary of research findings, applying technology to help in teaching and learning It enhances real-life learning for nursing students in the 21st century learning era, it increases real-life learning for nursing students, providing them confidence in their nursing profession.